Porous Metal Oxides as Gas Sensors - Tiemann, Michael (Chemistry - A European Journal)
Semiconducting metal oxides are frequently used as gas-sensing materials. Apart from large surface-to-volume ratios, well-defined and uniform pore structures are particularly desired for improved sensing performance. This article addresses the role of some key structural aspects in porous gas sensors, such as grain size and agglomeration, pore size or crack-free film morphology. New synthesis concepts, for example, the utilisation of rigid matrices for structure replication, allow to control these parameters independently, providing the opportunity to create self-diagnostic sensors with enhanced sensitivity and reproducible selectivity.